Study the Impact of Silica Nanoparticles on the Properties of Several Dyes for the Fabrication of a Random Laser Gain Medium - Noor Y. Khudair*; Mohammed K. Dhahir (Iraqi Journal of Laser, 2023)
Random laser gain media is synthesized with different types of dye at the same concentration (1×10-3 M) as an active material and silicon dioxide NPs (silica SiO2) as scatter centers through the Sol-Gel technique. The prepared samples are tested with UV–Vis spectroscopy, Fluorescence Spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), and Energy Dispersive X-ray Diffraction (EDX). The end result demonstrates that doped dyes with silica nanoparticles at a concentration of 0.0016 mol/ml have lower absorbance and higher fluorescence spectra than pure dyes. FESEM scans revealed that the morphology of nanocrystalline silica is clusters of nano-sized spherical particles in the range (25-67) nm. It is concluded that the various dyes with SiO2 as a scattering center can be proposed to build laser media.